Flame-retardant nylon cable sheath material and preparation method thereof
By using melamine, silica and chitosan composite materials as flame retardants and modifying nylon with crosslinking agents, the problem of nylon products melting at instantaneous high temperature was solved, and a nylon cable sheath material with excellent high temperature resistance, flame retardant and mechanical properties was obtained.
Patent Information
- Application Number
- CN202510049302.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Polyamide (nylon) products melt at instantaneously high temperature, causing failure of electrical components and causing accidents. The existing technology is difficult to effectively solve this problem.
Melamine, silica and chitosan composite materials are used as flame retardant, and nylon is cross-linked and modified with cross-linking agent to form a flame retardant nylon cable sheath material.
The obtained flame-retardant nylon cable sheath material has excellent high temperature resistance, flame retardant properties and mechanical properties, which can effectively prevent material melting caused by local instantaneous high heat and improve safety.
Abstract
Description
Technical Field
[0001] The present application relates to the field of nylon technology, and more specifically, to a flame retardant nylon cable sheath material and a preparation method thereof. Background Art
[0002] Polyamide (PA), commonly known as nylon, is the largest, most diverse and most widely used of the five major engineering plastics. In the field of communication optical cables, nylon 6 has outstanding weather resistance, good low temperature resistance, dimensional stability and is resistant to termites and mice. It is an excellent material for cable sheaths and is widely used in optical fiber communication cable sheaths and large-size power cable sheaths.
[0003] For thermoplastic engineering plastics, melting and plasticization at a certain temperature can facilitate molding of various structural types of parts, which is a significant advantage of plastics over thermosetting plastics. However, for polyamide products, they cannot compete with thermosetting plastics in terms of instantaneous high temperature resistance, which limits their application scenarios. Especially in electrical components, if a cable short-circuit occurs or encounters an open flame, the cable will be locally heated instantly, causing the PA material to melt instantly, the part to fail, and cause an accident. Summary of the invention
[0004] In order to solve the above problems, the present application provides a flame retardant nylon cable sheath material and a preparation method thereof, which adopts a material composed of melamine, silica and chitosan as a flame retardant, and uses a cross-linking agent to cross-link and modify the nylon. The flame retardant nylon cable sheath material obtained in this way not only has excellent high temperature resistance and flame retardant properties, but also has high mechanical properties.
[0005] In a first aspect, the present application provides a flame retardant nylon cable sheath material, comprising the following components in parts by weight: 5-95 parts of PA65, 4.5-7.7 parts of melamine-carboxylated silica modified chitosan composite, 0.3-0.6 parts of cross-linking agent, 0.3-0.6 parts of lubricant, and 1-1.8 parts of antioxidant.
[0006] This application uses PA6 as the base material and adds a set amount of melamine-carboxylated silica modified chitosan composite material, in which melamine can delay ignition by endothermic dissociation in the early stage of material combustion, and the nitrogen produced by its combustion can also act as an inert diluent to reduce the intensity of the flame. In addition, it can also produce a carbon layer during the combustion process to isolate air and combustibles. During the combustion process, silica will form a tight and stable silicon-containing carbon layer. This carbon layer can not only prevent the escape of combustible substances decomposed by combustion, but also play a role in heat insulation and oxygen isolation, thereby preventing the thermal decomposition of polymer materials and achieving flame retardant and low smoke effects. Chitosan is a linear polysaccharide composed of multiple amino glucosamine molecules connected by β-1,4-glycosidic bonds. This structure enables chitosan to form a stable carbon layer at high temperature, thereby playing a role in heat insulation and oxygen isolation, and effectively preventing the spread of flames. In addition, carboxylated silica modified chitosan can also adsorb metal elements such as nickel, lead, and cadmium that may be precipitated from cable combustion, greatly reducing the impact of cable combustion on the environment.
[0007] This application combines melamine, silicon dioxide and chitosan into one, so that the three complement each other and effectively improve the flame retardant properties of the flame retardant nylon cable sheath material. It is also environmentally friendly. The composite material can also improve the stability of chitosan in the material preparation process and the dispersion effect of silicon dioxide in the system. Compared with the method of adding the three separately, the composite material can reduce the degree of instantaneous melting of the PA material caused by local instantaneous high heat, thereby effectively improving the high temperature resistance of the flame retardant nylon cable sheath material. On this basis, a set amount of cross-linking agent is also added in this application. The cross-linking agent is used to cross-link and modify PA6 on the one hand to improve the comprehensive performance of PA6. On the other hand, it can also bond and stabilize the melamine-carboxylated silica-modified chitosan composite dispersed in PA6, so as to enable the composite to play an effective role and further improve the high temperature resistance and mechanical properties of the flame-retardant nylon cable sheath material. Preferably, the preparation method of the melamine-carboxylated silica modified chitosan composite comprises the following steps: taking melamine and dispersing it evenly with methanol, then adding carboxylated silica modified chitosan to react, and filtering and drying to obtain the composite.
[0008] By adopting the above technical scheme, the present application uses methanol as a medium to facilitate subsequent volatilization recovery and reuse. The -COOH in the carboxylated silica is acidic and can react with the -NH2 in melamine to form an amide bond (-CONH-), thereby compounding melamine with the carboxylated silica-modified chitosan. The obtained composite material has a multi-layer network structure, which is beneficial to increase the specific surface area to reduce the probability of its precipitation from PA6. The above preparation process is simple to operate and has high operability.
[0009] Preferably, the weight ratio of the melamine to the carboxylated silica modified chitosan composite is 9:1.
[0010] By adopting the above technical scheme, the present applicant has found through experimental research that the melamine-carboxylated silica modified chitosan composite prepared according to the above weight ratio has more excellent high temperature resistance, flame retardancy and mechanical properties, and therefore it is further preferred.
[0011] Preferably, the preparation method of the carboxylated silica-modified chitosan comprises the following steps: dispersing silica in an ether solution, slowly adding succinic acid glycoside, filtering and drying after the reaction is completed to obtain carboxylated silica; dispersing chitosan in n-butanol, slowly adding carboxylated silica, filtering and drying after the reaction is completed to obtain the carboxylated silica-modified chitosan.
[0012] Preferably, the weight ratio of the carboxylated silica to the chitosan is 1.2:1.
[0013] Adopting the above technical scheme, the present application uses ether and succinic acid glycoside to firstly carboxylate silicon dioxide, and then uses n-butanol to achieve the modification of chitosan. The reaction process is controllable, and carboxylated silicon dioxide-modified chitosan with a higher yield can be harvested. Conventionally, six parts of silicon dioxide are used to match one part of chitosan. In the present application, an appropriate excess of carboxylated silicon dioxide is used to effectively ensure that chitosan is fully modified, avoiding the occurrence of free chitosan and affecting the flame-retardant nylon cable sheath material, and the excess carboxylated silicon dioxide can also be combined with melamine as a flame retardant to ensure the excellent flame retardant properties of the flame-retardant nylon cable sheath material.
[0014] Preferably, the cross-linking agent is selected from one or more of triallyl cyanurate, triallyl isocyanurate, trimethallyl isocyanurate, and trimethylolpropane trimethacrylate.
[0015] Preferably, the cross-linking agent is a mixture of triallyl isocyanurate and trimethallyl isocyanurate in a weight ratio of 3:1.
[0016] By adopting the above technical scheme, triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethylallyl isocyanurate (TMAIC), and trimethylolpropane trimethacrylate (TMPTMA) are all common crosslinking agents for nylon, and they can all play a good crosslinking effect in this application to obtain flame-retardant nylon cable sheath materials with excellent performance. Among them, when the crosslinking agent is a mixture of triallyl isocyanurate and trimethylallyl isocyanurate in a weight ratio of 3:1, the performance of the flame-retardant nylon cable sheath material obtained is significantly better than others, so it is further preferred.
[0017] Preferably, the lubricant is selected from one or more of silicone, stearic acid, stearate, pentaerythritol stearate, organosiloxane, polyester wax, mesoamide, and alkane wax.
[0018] Preferably, the antioxidant is selected from one or more of hindered phenol and phosphite antioxidants.
[0019] In a second aspect, the present application provides a method for preparing a flame retardant nylon cable sheath material, comprising the following steps: A set amount of PA6, melamine-carboxylated silica modified chitosan composite, crosslinking agent and lubricant are placed in a vacuum reactor, and fully stirred and mixed at a temperature of 150-160°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. After the irradiation is completed, a set amount of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder at an extrusion temperature of 250-280°C to obtain the flame-retardant nylon cable sheath material.
[0020] In the present application, PA6 is mixed with a melamine-carboxylated silica modified chitosan composite, a crosslinking agent and a lubricant and then directly subjected to irradiation crosslinking, thereby reducing the difficulty of dispersing the nylon with the melamine-carboxylated silica modified chitosan composite after crosslinking. In addition, the system stability of the nylon and the composite after dispersion can be further increased, thereby obtaining a flame-retardant nylon cable sheath material with better high temperature resistance and mechanical properties.
[0021] In summary, this application has the following beneficial effects: 1. This application uses a composite material of melamine, silicon dioxide and chitosan as a flame retardant, and uses a cross-linking agent to cross-link and modify nylon. The flame-retardant nylon cable sheath material obtained not only has excellent high temperature resistance and flame retardant properties, but also has high mechanical properties; 2. This application further improves the high temperature resistance, flame retardancy and mechanical properties of the flame retardant nylon cable sheath material by strictly controlling the components and dosage.
[0022] 3. The preparation method of the present application further increases the system stability of nylon and the composite material after dispersion by pre-mixing the raw materials and irradiating and cross-linking, thereby obtaining a flame-retardant nylon cable sheath material with better high temperature resistance and mechanical properties. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0024] The raw materials and reagents used in this application are all purchased from commercial products. The key parameters of the main raw materials are as follows: PA6, using German BASF B3S low-viscosity pure resin, flame retardant performance HB; Melamine, analytical grade, with an active ingredient content of 99%, was purchased from Henan Xinzhiyuan Chemical Products Co., Ltd.; Silicon dioxide, using dispersible nano-silicon dioxide particles, was purchased from Henan Nanotechnology Co., Ltd.; Chitosan (CTS), with a deacetylation degree of 96%, was purchased from Shaanxi Changji Fu Biotechnology Co., Ltd.; Ether, succinic anhydride, n-butanol, and methanol were all analytically pure; A cross-linking agent selected from one or more of triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethylallyl isocyanurate (TMAIC), and trimethylolpropane trimethacrylate (TMPTMA), and preferably a cross-linking agent prepared by mixing triallyl isocyanurate (TAIC) and trimethylallyl isocyanurate (TMAIC) in a weight ratio of 3:1; The lubricant is selected from one or more of silicone, stearic acid, stearate, pentaerythritol stearate, organosiloxane, polyester wax, inter amide, and alkane wax. The present application specifically uses stearic acid with model number SA1801 as an example for explanation; The antioxidant is selected from one or more of hindered phenols and phosphite antioxidants. The present application specifically takes a mixture of antioxidant 1098 and antioxidant 168 of Tianjin RIANOX in a weight ratio of 1:1 as an example for explanation.
[0025] The present application is further described in detail below in conjunction with embodiments and comparative examples. Example Example 1
[0026] This embodiment provides a method for preparing a flame retardant nylon cable sheath material, comprising the following steps: (1) Preparation of carboxylated silica-modified chitosan Take 75g of silica and disperse it in 5L of ether solution, slowly add 50g of succinate glycoside, react at a constant temperature of 20°C for 2h, filter after the reaction is completed to obtain a solid powdery substance, place it in a constant temperature box at 40°C and vacuum dry it for 4h to obtain carboxylated silica; take 10g of chitosan and disperse it in 2L of n-butanol and stir for 0.5h, slowly add 12g of the above carboxylated silica, stir and heat to 65°C and react at a constant temperature for 7h, cool to room temperature, use a vacuum pump to filter to obtain a solid powdery substance, place it in a constant temperature box at 70°C and vacuum dry it for 6h to obtain carboxylated silica modified chitosan.
[0027] (2) Preparation of melamine-carboxylated silica modified chitosan composites Take 90g of melamine and disperse it evenly with 1L of methanol, then add 10g of carboxylated silica modified chitosan, and stir the reaction at a constant temperature of 20°C until a white precipitate gradually precipitates out of the system. Continue stirring the reaction for 1h and then stop. After standing for 1h, filter it out, wash the sample with methanol 3 times and then dry it to obtain a melamine-carboxylated silica modified chitosan composite.
[0028] (3) Preparation of flame-retardant nylon cable sheath materials 800g of PA6, 65g of melamine-carboxylated silica modified chitosan composite, 5g of cross-linking agent and 5g of lubricant are placed in a vacuum reactor, wherein the cross-linking agent is prepared by mixing triallyl isocyanurate TAIC and trimethylallyl isocyanurate TMAIC in a weight ratio of 3:1, and the mixture is fully stirred and mixed at a temperature of 155°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. The irradiation processing conditions are electron beam, and the irradiation dose is 100kGy. After the irradiation is completed, 15g of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder. The screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 350rpm, and the extrusion temperature is 270°C, so as to obtain a flame-retardant nylon cable sheath material.
[0029] The obtained flame-retardant nylon cable sheath material was put into an injection molding machine for extrusion. The extrusion temperature was 240° C. The thickness of the extruded cable sheath was 1.5±0.01 mm, and the flame-retardant nylon cable sheath was obtained as a test sample. Example 2
[0030] Based on the method of Example 1, this example adjusts the component dosage and process parameters for preparing the flame-retardant nylon cable sheath material, as follows: 550g of PA6, 45g of melamine-carboxylated silica modified chitosan composite, 3g of cross-linking agent and 3g of lubricant are placed in a vacuum reactor, wherein the cross-linking agent is prepared by mixing triallyl isocyanurate TAIC and trimethylallyl isocyanurate TMAIC in a weight ratio of 3:1, and the mixture is fully stirred and mixed at a temperature of 150°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. The irradiation processing conditions are electron beam, and the irradiation dose is 100kGy. After the irradiation is completed, 10g of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder. The screw length-diameter ratio of the twin-screw extruder is 40:1, the screw speed is 350rpm, and the extrusion temperature is 250°C, so as to obtain a flame-retardant nylon cable sheath material. Example 3
[0031] In this embodiment, based on the method of embodiment 1, the amount of components used in preparing the flame-retardant nylon cable sheath material is adjusted as follows: 700g of PA6, 57g of melamine-carboxylated silica modified chitosan composite, 4g of cross-linking agent and 4g of lubricant are placed in a vacuum reactor, wherein the cross-linking agent is prepared by mixing triallyl isocyanurate TAIC and trimethylallyl isocyanurate TMAIC in a weight ratio of 3:1, and the mixture is fully stirred and mixed at a temperature of 155°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. The irradiation processing conditions are electron beam, and the irradiation dose is 100kGy. After the irradiation is completed, 13g of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 40:1, a screw speed of 350rpm, and an extrusion temperature of 270°C to obtain a flame-retardant nylon cable sheath material. Example 4
[0032] Based on the method of Example 1, this example adjusts the component dosage and process parameters for preparing the flame-retardant nylon cable sheath material, as follows: 950g of PA6, 77g of melamine-carboxylated silica modified chitosan composite, 6g of cross-linking agent and 6g of lubricant are placed in a vacuum reactor, wherein the cross-linking agent is prepared by mixing triallyl isocyanurate TAIC and trimethylallyl isocyanurate TMAIC in a weight ratio of 3:1, and the mixture is fully stirred and mixed at a temperature of 160°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. The irradiation processing conditions are electron beam, and the irradiation dose is 100kGy. After the irradiation is completed, 18g of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 40:1, a screw speed of 350rpm, and an extrusion temperature of 280°C to obtain a flame-retardant nylon cable sheath material. Example 5
[0033] In this embodiment, based on the method of embodiment 1, the amount of components used in preparing the flame-retardant nylon cable sheath material is adjusted as follows: 800g of PA6, 60g of melamine-carboxylated silica modified chitosan composite, 5g of cross-linking agent and 5g of lubricant are placed in a vacuum reactor, wherein the cross-linking agent is prepared by mixing triallyl isocyanurate TAIC and trimethylallyl isocyanurate TMAIC in a weight ratio of 3:1, and the mixture is fully stirred and mixed at a temperature of 155°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. The irradiation processing conditions are electron beam, and the irradiation dose is 100kGy. After the irradiation is completed, 15g of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder. The twin-screw extruder has a screw length-to-diameter ratio of 40:1, a screw speed of 350rpm, and an extrusion temperature of 270°C to obtain a flame-retardant nylon cable sheath material.
[0034] In Example 6-7, based on the method of Example 1, the preparation parameters of the melamine-carboxylated silica modified chitosan composite were adjusted. In Example 6, the weight ratio of melamine to carboxylated silica modified chitosan composite was adjusted to 8:1; in Example 7, the weight ratio of melamine to carboxylated silica modified chitosan composite was adjusted to 10:1.
[0035] In Example 8-9, the preparation parameters of carboxylated silica-modified chitosan were adjusted based on the method of Example 1. In Example 8, the weight ratio of carboxylated silica to chitosan was adjusted to 1:1; and in Example 9, the weight ratio of melamine to carboxylated silica-modified chitosan composite was adjusted to 1.5:1.
[0036] In Examples 10-14, based on the method of Example 1, the crosslinking agent in the flame-retardant nylon cable sheath material component is adjusted. Among them, the crosslinking agent used in Example 10 is triallyl cyanurate TAC; the crosslinking agent used in Example 11 is triallyl isocyanurate TAIC; the crosslinking agent used in Example 12 is trimethylallyl isocyanurate TMAIC; the crosslinking agent used in Example 13 is a mixture of triallyl isocyanurate TAIC and trimethylallyl isocyanurate TMAIC at a weight ratio of 1:1; the crosslinking agent used in Example 14 is a mixture of triallyl isocyanurate TAIC and trimethylolpropane trimethacrylate TMPTMA at a weight ratio of 3:1. Embodiment 15
[0037] In this embodiment, based on the method of embodiment 1, the preparation method of the flame-retardant nylon cable sheath material is adjusted, that is, extrusion granulation is first performed and then irradiation cross-linking is performed. The specific steps are as follows: 800g of PA6, 65g of melamine-carboxylated silica modified chitosan composite, 5g of cross-linking agent, 5g of lubricant and 15g of antioxidant were stirred evenly and added into a twin-screw extruder for granulation. The aspect ratio of the screw of the twin-screw extruder was 40:1, the screw speed was 350rpm, and the extrusion temperature was 270°C. The obtained particles were put into an injection molding machine for extrusion. The extrusion temperature was 240°C. The thickness of the extruded cable sheath was 1.5±0.01mm. Then, irradiation treatment was performed. The irradiation processing conditions were electron beam and the irradiation dose was 100kGy. Flame-retardant nylon cable sheath was obtained as the sample to be tested. Comparative Example Comparative Example 1
[0038] In this comparative example, based on the method of Example 1, the melamine-carboxylated silica modified chitosan composite material was replaced with a mixture of equal amounts of melamine, carboxylated silica and chitosan, namely, 58.5 g of melamine, 3.55 g of carboxylated silica and 2.95 g of chitosan were stirred and mixed. Comparative Example 2
[0039] In this comparative example, based on the method of Example 1, the melamine-carboxylated silica modified chitosan composite material was replaced with an equal amount of carboxylated silica modified chitosan. Comparative Example 3
[0040] In this comparative example, based on the method of Example 1, the melamine-carboxylated silica modified chitosan composite material was replaced with an equal amount of chitosan phosphate melamine salt flame retardant. Performance testing
[0041] The samples prepared in the above-mentioned Examples 1-15 and Comparative Examples 1-3 were subjected to the following performance tests. The test results are shown in Table 1 below.
[0042] 1. High temperature resistance: Use electric soldering iron to test (melting depth). The test method is electric soldering iron, heating contact diameter 2mm, height 5mm, temperature 400℃, vertical contact with the surface of the sample to be tested, load 1kg, keep for 3min, remove the test head, and measure the melting depth of the contact point (μm); 2. Flame retardant performance: It is expressed by the limiting oxygen index (%) of the oxygen index test and the flame retardant grade (level) of the vertical burning method test. When testing the oxygen index, the sample to be tested is cut into strips of 50mmx6mm, and the oxygen concentration is 30%; when testing the vertical burning method, 1.6mm is burned; the higher the limiting oxygen index and the flame retardant grade, the better the flame retardant performance; 3. Mechanical properties: expressed by tensile strength (MPa). The greater the tensile strength, the better the mechanical properties.
[0043] Table 1 Performance test table of Examples 1-15 and Comparative Examples 1-3 Melt depth / μm Limiting oxygen index / % Flame retardant grade / level Tensile strength / MPa Example 1 10 38.5 V0 81.2 Example 2 15 33.2 V0 78.5 Example 3 11 37.1 V0 79.0 Example 4 12 36.7 V0 79.5 Example 5 23 30.7 V0 73.1 Example 6 20 35.9 V0 78.6 Example 7 17 37.0 V0 74.9 Example 8 34 35.2 V0 70.5 Example 9 13 36.4 V0 73.8 Example 10 38 37.8 V0 67.2 Embodiment 11 26 37.8 V0 69.7 Example 12 31 37.9 V0 69.0 Embodiment 13 19 38.2 V0 72.2 Embodiment 14 24 38.0 V0 73.1 Embodiment 15 18 36.7 V0 78.9 Comparative Example 1 153 23.8 V1 41.5 Comparative Example 2 109 25.1 V1 46.5 Comparative Example 3 64 30.6 V0 48.2 Combined with Table 1 above, by comparing the test results of Examples 1-15 of the present application with those of Comparative Examples 1-3, it can be obtained that, compared with the method of adding the three separately, adding carboxylated silica-modified chitosan alone, or using other composite flame retardants such as chitosan phosphate melamine salt flame retardants, the present application uses a composite material of melamine, silica and chitosan as one, which can better reduce the degree of instantaneous melting of the PA material caused by local instantaneous high heat, thereby effectively improving the high temperature resistance of the flame retardant nylon cable sheath material; and then using a cross-linking agent to cross-link and modify the nylon, the flame retardant nylon cable sheath material obtained thereby not only has excellent high temperature resistance and flame retardant properties, but also has high mechanical properties.
[0044] By comparing the test results of Example 1 with those of Examples 6 to 7, it can be obtained that in the melamine-carboxylated silica modified chitosan composite of the present application, when the weight ratio of melamine to carboxylated silica modified chitosan composite is 9:1, a flame retardant nylon cable sheath material with better high temperature resistance, flame retardant properties and mechanical properties can be obtained.
[0045] By comparing the test results of Example 1 with those of Examples 8 to 9, it can be obtained that in the melamine-carboxylated silica modified chitosan composite of the present application, when the weight ratio of carboxylated silica to chitosan is 1.2:1, a flame-retardant nylon cable sheath material with better high temperature resistance, flame retardant properties and mechanical properties can be obtained.
[0046] By comparing the test results of Example 1 with those of Examples 10-14, it can be found that in the flame retardant nylon cable sheath material component of the present application, when the cross-linking agent is a mixture of triallyl isocyanurate and trimethallyl isocyanurate in a weight ratio of 3:1, the performance of the flame retardant nylon cable sheath material obtained is significantly better than others, so it is further preferred.
[0047] By comparing the test results of Example 1 with those of Example 15, it can be concluded that the present application directly irradiates and crosslinks PA6 after mixing it with melamine-carboxylated silica modified chitosan composite, crosslinking agent and lubricant, and can obtain a flame-retardant nylon cable sheath material with better high temperature resistance and mechanical properties. Compared with the method of irradiating and crosslinking after making the finished product, it can also avoid irradiation denaturation of other materials in the cable sheath, thereby meeting the use requirements of the cable.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A flame retardant nylon cable sheath material, characterized in that: The invention comprises the following components in parts by weight: 55-95 parts of PA6, 4.5-7.7 parts of melamine-carboxylated silicon dioxide modified chitosan composite material, 0.3-0.6 parts of crosslinking agent, 0.3-0.6 parts of lubricant and 1-1.8 parts of antioxidant.
2. The flame-retardant nylon cable sheath material according to claim 1, characterized in that: The preparation method of the melamine-carboxylated silicon dioxide modified chitosan composite material comprises the following steps: taking melamine and dispersing it evenly with methanol, then adding carboxylated silicon dioxide modified chitosan to react, and filtering and drying to obtain the composite material.
3. The flame retardant nylon cable sheath material according to claim 2, characterized in that: The weight ratio of the melamine to the carboxylated silicon dioxide modified chitosan composite material is 9:
1.
4. The flame retardant nylon cable sheath material according to claim 2, characterized in that: The preparation method of carboxylated silicon dioxide modified chitosan comprises the following steps: dispersing silicon dioxide in an ether solution, slowly adding succinic acid glycoside, filtering and drying after the reaction is completed to obtain carboxylated silicon dioxide; dispersing chitosan in n-butanol, slowly adding carboxylated silicon dioxide, filtering and drying after the reaction is completed to obtain the carboxylated silicon dioxide modified chitosan.
5. The flame retardant nylon cable sheath material according to claim 4, characterized in that: The weight ratio of the carboxylated silicon dioxide to the chitosan is 1.2:
1.
6. The flame retardant nylon cable sheath material according to claim 1, characterized in that: The cross-linking agent is selected from one or more of triallyl cyanurate, triallyl isocyanurate, trimethallyl isocyanurate, and trimethylolpropane trimethacrylate.
7. The flame retardant nylon cable sheath material according to claim 6, characterized in that: The cross-linking agent is prepared by mixing triallyl isocyanurate and trimethallyl isocyanurate in a weight ratio of 3:
1.
8. The flame retardant nylon cable sheath material according to claim 1, characterized in that: The lubricant is selected from one or more of silicone, stearic acid, stearate, pentaerythritol stearate, organosiloxane, polyester wax, mesoamide, and alkane wax.
9. The flame retardant nylon cable sheath material according to claim 1, characterized in that: The antioxidant is selected from one or more of hindered phenol and phosphite antioxidants.
10. The method for preparing the flame-retardant nylon cable sheath material according to any one of claims 1 to 9, characterized in that: The following steps are involved: A set amount of PA6, melamine-carboxylated silica modified chitosan composite, crosslinking agent and lubricant are placed in a vacuum reactor, and fully stirred and mixed at a temperature of 150-160°C. The obtained mixture is cooled to room temperature, then flattened and irradiated. After the irradiation is completed, a set amount of antioxidant is added and mixed evenly. Finally, granulation is carried out through a twin-screw extruder at an extrusion temperature of 250-280°C to obtain the flame-retardant nylon cable sheath material.
Citation Information
Patent Citations
Flame-retardant modified nylon and preparation method thereof
CN107903622A
High-gloss flame-retardant antibacterial polypropylene composite material and preparation method thereof
CN113214564A
Biomass flame retardant, water-based flame-retardant coating as well as preparation method and application of water-based flame-retardant coating
CN113493624A
Preparation method and application of flame-retardant reinforced polyamide composite material for irradiation crosslinking
CN114316580A
Micro-irradiation flame-retardant transparent nylon cable sheath material and preparation method thereof
CN115948048A